Numerical simulation of reactive processes in an experiment with partially saturated bentonite - Xie, Mingliang; Bauer, Sebastian; Kolditz, Olaf; Nowak, Thomas; Shao, Hua (Journal of contaminant hydrology, 2006)
Bentonites are preferred materials for use as engineered barriers for high-level nuclear waste repositories. Simulation of geochemical processes in bentonite is therefore important for long-term safety assessment of those repositories. In this work, the porewater chemistry of a bentonite sample subject to simultaneous heating and hydration, as studied by Cuevas et al. [Cuevas, J., Villar, M., Fernández, A., Gómez, P., Martín, P., 1997. Porewaters extracted from compacted bentonite subjected to simultaneous heating and hydration. Applied Geochemistry 12, 473–481.], was assessed with a non-isothermal reactive transport model by coupling the geochemical software PHREEQC2 with the object-oriented FEM simulator GeoSys/RockFlow. Reactive transport modelling includes heat transport, two-phase flow, multicomponent transport and geochemical reactions in the liquid phase, i.e. ion exchange, mineral dissolution/precipitation and equilibrium reactions. Simulations show that the easily soluble minerals in bentonite determine the porewater chemistry. Temperature affects both two-phase flow and geochemical reactions. Porosity change due to dissolution/precipitation is low during the experiment. However, changes of the effective porosity caused by bentonite swelling can be very large. The simulated results agree well with the experimental data.